Comprehensive in silico identification of impacts of ACE2 SNPs on COVID-19 susceptibility in different populations - Paniri, Alireza (Gene Rep, 2021)
The COVID-19 pandemic emerges a reminder that wide spectrum discrepancy in response to SARS-CoV-2 infection and antiviral drugs among different populations might be due to their different ACE2 SNPs and/or miRNAs profile. ACE2 is the major component for SARS-CoV-2s' cell entry, and disruption of its 3D structure could influence virus-ACE2 interaction. In this study we aimed to investigate the consequence of 16,860 SNPs within ACE2 on its expression as well as protein folding, function, and stability by using several beneficial bioinformatics tools. Only 64 SNPs including 60 intronic, and 4 missense showed different frequencies among different populations. Two missense SNPs including rs149039346 and rs147311723 have been predicted to strongly influence the function and stability of ACE2. rs1514283 creates new acceptor splice site. Also, rs4646175 creates new donor and acceptor splice site. PolymiRTS, and miRSNPs have predicted that rs3746444, rs113808830, and rs3751304 showed a MAF > 0.001, and disrupted mRNA target sites or mRNA function. Finally, rs3746444 hsa-miR-499a-3p, rs113808830 hsa-miR-4532, rs3751304 hsa-miR-6763-3p and hsa-miR-26b-5p were strongly hybridized with ACE2 and might influence its function. Collectively, this study shed some light on fundamental roles of ACE2 SNPs for its interaction with COVID-19, and consequently susceptibility to virus. Therefore, different responses of patients with COVID-19 to ACE2 blocker drugs might be due to their unique ACE2 SNPs. We further discussed the impact of SNPs on miRNAs profile as a factor that may modulate drug response or susceptibility to COVID-19.